Technical challenges and future direction for high-efficiency metal hydride thermal energy storage systems - Ward, P.; Corgnale, C.; Teprovich, J.; Motyka, T.; Hardy, B.; Sheppard, Drew; Buckley, Craig; Zidan, R. (Springer, 2016)
© 2016. Springer-Verlag Berlin Heidelberg. Recently, there has been increasing interest in thermal energy storage (TES) systems for concentrated solar power (CSP) plants, which allow for continuous operation when sunlight is unavailable. Thermochemical energy storage materials have the advantage of much higher energy densities than latent or sensible heat materials. Furthermore, thermochemical energy storage systems based on metal hydrides have been gaining great interest for having the advantage of higher energy densities, better reversibility, and high enthalpies. However, in order to achieve higher efficiencies desired of a thermal storage system by the US Department of Energy, the system is required to operate at temperatures >600 °C. Operation at temperatures >600 °C presents challenges including material selection, hydrogen embrittlement and permeation of containment vessels, appropriate selection of heat transfer fluids, and cost. Herein, the technical difficulties and proposed solutions associated with the use of metal hydrides as TES materials in CSP applications are discussed and evaluated.